IDENTIFIKASI DAN PREVALENSI CACING USUS PADA MURID SDN 2 SALOYA KECAMATAN SINDUE TOMBUSABORA SULAWESI TENGAH - WAHYUDIN ABD KARIM; ELIJONNAHDI ELIJONNAHDI (Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Luwuk, 2017)
Intestinal worm disease is still a public health problem in Indonesia. This disease can be found in children under five until fourthen years old. The aim of the present study was to prevalence of intestinal worm infection in children. The fresh faecal samples were collected from 56 childrens and observed by a Kato-Katz technique. The faecal of childrens were collected in SDN 2 Saloya village, Central Sulawesi. The result of identification on intestinal worm showed that 23 samples (41.07%) were found positive infections and 33 samples (58.93%) were found negetive infections. The prevelence of intestinal worm in class two were highest than all of them class. The prevalence of intestinal worm in females were highest than male. The totality sample identification of faecal childrens to Kato-Katz technique were found two genera i.e Trichuris, Ascaris, and other worm.Keywords: Intestinal worm prevalence, childrens